Gnostics of the North, or Music To Recolonize Your Anxious Capitalist Dreams By - Seth Kim-Cohen (Law Text Culture, 2020)
In 1975, the Venezuelan terrorist known as Carlos (born Ilich Ramírez Sánchez) and six accomplices, calling themselves the Arm of the Arab Revolution, raided the annual meeting of the Organization of Petroleum Exporting Countries in Vienna. Demanding the liberation of Palestine, they took more than sixty hostages, including the Oil and Energy Ministers of most of the OPEC member states. The OPEC kidnapping is the most notorious entry in Carlos’s résumé of political violence. And the geopolitical complexities of the event, its motivations, and its ramifications are far-reaching and profound.